Analisis Motivasi Belajar Siswa Kelas V SDN Cibabat Mandiri 2 pada Materi Sudut dalam Mata Pelajaran Matematika dengan Bantuan Media Polypad - Ismi Amelia; Indah Dahlia; Etrin Rhut Nugraheni; Ratna Sariningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
his study aims to determine the learning motivation of grade V students in angular material in the subject of Mathematics with the help of Polypad media. The research method used in this study is a descriptive method with a quantitative approach and data analysis using Microsoft Excel software. The sample used in this study was 30 students in grade V of SDN Cibabat Mandiri 2. The instrument used was in the form of a questionnaire consisting of 5 indicators that included 15 questions, consisting of 8 positive questions and 7 negative questions. The results showed that the use of Polypad media significantly increased students' motivation to learn, with an average motivation percentage reaching 78%, which was in the